USING COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH THROUGH SMALL GROUP DISCUSSION AS A DEVICE TO STIMULATE THE STUDENTS TO SPEAK IN ENGLISH - Muhammad Astrianto Setiadi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
This study was conducted to find out whether or not the using of Communicative Language Teaching (CLT) Approach through Small Group Discussion effective to stimulate the students to speak in English than the conventional way, and also to improve the teacher awareness to use an effective approach in teaching English, especially in teaching speaking skill. This study employed a Pre-Experimental research method with One Group Pre-test and Post-test Design. The data obtained from the test was analyzed quantitatively and then it’s result was compared with the questionnaire to know whether the students interested in learning speaking by using Communicative Language Teaching (CLT) Approach or not. The mean score obtained from Pre-test was 2, 84 and post-test were 6, 01. The data showed that the student’s speaking skills in post-test were higher than the pre-test. The data obtained from questionnaire showed the mean score 78, 67. It means that the students were highly interested in the application of speaking materials through Communicative Language Teaching Approach through small group discussion.Keyword: Communicative Language Teaching Approach, Small Group discussion, speaking.